1979
DOI: 10.1071/bi9790343
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of the Plasma Steroid Concentration Profiles and Wool Growth Responses After Administration of Two Forms of Dexamethasone to Sheep

Abstract: Sheep were treated with dexamethasone (1) as the water-soluble 21-phosphate intravenously or (2) subcutaneously, and (3) as the water-insoluble parent compound subcutaneously.In (1) the infusion was continued for 8 days and plasma· concentrations of dexamethasone exceeded 40 ng/ml. The analogue quickly disappeared from the circulation after the infusion was stopped. Compared with pretreatment values wool growth decreased by about 80 % 17 days after cessation of the infusion. By 31 days, wool growth was almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

1979
1979
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 7 publications
0
18
1
Order By: Relevance
“…Corticosteroid treatment of ISIF animals provided a crude method of immuno-suppression and has previously been shown to have a wide range of effects on metabolism including a net catabolic effect that may result in reduced wool production (Panaretto, 1979) and decreased fractional synthesis rates of protein in the muscle and intestine (Huang et al, 1998;Turini et al, 2003). Their effect on intake in sheep has been varied, with small single doses of 0.1 mg dexamethasone/kg (equivalent to 0.5 mg methylprednisolone) stimulating short-term increases (Adams and Sanders, 1992) while larger single doses of 6 mg dexamethasone/kg have resulted in a short-term depression of intake (Panaretto, 1979).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Corticosteroid treatment of ISIF animals provided a crude method of immuno-suppression and has previously been shown to have a wide range of effects on metabolism including a net catabolic effect that may result in reduced wool production (Panaretto, 1979) and decreased fractional synthesis rates of protein in the muscle and intestine (Huang et al, 1998;Turini et al, 2003). Their effect on intake in sheep has been varied, with small single doses of 0.1 mg dexamethasone/kg (equivalent to 0.5 mg methylprednisolone) stimulating short-term increases (Adams and Sanders, 1992) while larger single doses of 6 mg dexamethasone/kg have resulted in a short-term depression of intake (Panaretto, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…Their effect on intake in sheep has been varied, with small single doses of 0.1 mg dexamethasone/kg (equivalent to 0.5 mg methylprednisolone) stimulating short-term increases (Adams and Sanders, 1992) while larger single doses of 6 mg dexamethasone/kg have resulted in a short-term depression of intake (Panaretto, 1979). The chronic weekly administrations of 1.3 mg/kg LW to IS animals in the current study, perhaps surprisingly, did not cause a reduction in wool growth, but did stimulate fat deposition, reduced muscle deposition and had no significant effect on intake, observations that are consistent with those of Greer et al (2005b).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma dexamethasone concentrations were determined by radioimmunoassay (Panaretto 1979). The limit of sensitivity of the assay was 3· 1 ng ml-'.…”
Section: Dexamethasone Assaymentioning
confidence: 99%
“…Adrenal glucocorticoid hormones or their analogues are known to stimulate or inhibit anagen wool follicles (Chapman and Bassett 1970;Panaretto 1979). In order to induce shedding of the majority of wool fibres, Panaretto and Wallace (1978a) and Panaretto (1979) found that it was necessary to maintain elevated glucocorticoid concentrations in the plasma of Merino sheep for 8 days.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation